Occurrence of woolly cupgrass (Eriochloa villosa /Thunb./ Kunth) in Hajdú-Bihar county, Hungary - Somogyi, Noémi; Szabó, László; Dávid, István (Acta Agraria Debreceniensis, 2011)
Woolly cupgrass (Eriochloa villosa /Thunb./ Kunth) is native to East Asia, it spreads in several parts of the World and causes difficulties in plant protection, especially in maize. Difficulties in control of Eriochloa villosa originated from several reasons: seeds continue to germinate later in the season, significant part of seeds emerges from a deep layer of the soil, and the species is less susceptible to some herbicides applied to maize than other annual grass weeds. The first report on the occurrence of woolly cupgrass in Hungary was published in 2008, and it reported about the appearance of this species near to Gesztely village (Borsod-Abaúj-Zemplén county), however, no information has been added about spread of the weed in Hungary until now. A significant population was discovered next to Debrecen (Hajdú-Bihar county) in summer, 2011, and then weed associations were examined in maize, sunflower and stubble-fields on several km2 in the area to estimate the Eriochloa villosa infection. The weed species was found on every maize field bordering with a ground cover of 0.5-4%. Woolly cupgrass occurred inside of the 50% of maize fields, and reached a ground cover of 76% in case of most infected area, in addition it was found in sunflower and stubble-fields. The spread of woolly cupgrass is expected in this area, which requires the consideration of this species in the planning of weed management technologies.